The forest in medieval German literature ecocritical readings from a historical perspective - Classen, Albrecht 1956- (Ecocritical theory and practice, 2015)
By pursuing an ecocritical reading, The Forest in Medieval German Literature examines passages in medieval German texts where protagonists operated in the forest and found themselves either in conflictual situations or in refuge. By probing the way the individual authors dealt with the forest, illustrating how their characters fared in this sylvan space, the role of the forest proved to be of supreme importance in understanding the fundamental relationship between humans and nature. The medieval forest almost always introduced an epistemological challenge: how to cope in life, or how to find one's way in this natural maze. By approaching these narratives through modern ecocritical issues that are paired with premodern perspectives, we gain a solid and far-reaching understanding of how medieval concepts can aid in a better understanding of human society and nature in its historical context. This book revisits some of the best and lesser known examples of medieval German literature, and the critical approach used here will allow us to recognize the importance of medieval literature for a profound reassessment of our modern existence with respect to our own forests. ..